Perancangan Game Edukasi Pengenalan Makanan Sehat dan Tidak Sehat untuk Kesehatan Gigi Anak Berbasis Android - Muchamad Akbar Adi Sofiawinoto; Riskysari Meimaharani; Mukhamad Nurkamid (JUMINTAL: Jurnal Manajemen Informatika dan Bisnis Digital, 2024)
Designing an Android-based educational game for introducing healthy and unhealthy foods for children's dental health is an application created with the aim of helping children maintain healthy teeth and mouth by choosing good and correct food, and also making it easier for parents to teach their children how to choose good and healthy food for children. So that children become enthusiastic about maintaining and learning about oral and dental health. Applications are created using the research and development method, where this method is a sequential software development process, where each work process continues from top to bottom, through phases in the process of System Requirements Analysis, System Design, System Implementation, System Testing, and System Maintenance. This application was created with the help of the Construct 2 application to build and develop the application and Adobe Photoshop was used to assist in creating the initial design of the application and also the logo for the application.